2012
DOI: 10.3177/jnsv.58.45
|View full text |Cite
|
Sign up to set email alerts
|

Gallated Form of Tea Catechin, Not Nongallated Form, Increases Fecal Starch Excretion in Rats

Abstract: Summary This study was carried out to elucidate the structural advantage of a gallated form of tea catechin on modulating bioavailability of dietary starch in rats. Animal studies demonstrated that the addition of 0.5% (w/w) ( Ϫ )-epigallocatechin gallate (EGCG) to the diet brought about a significant increase in the starch content in the feces collected for 2 d at the fourth week of feeding over that with the control diet. Of the gross starch that the rats consumed from their respective diets during the fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The concentrations of undigested starch in the feces were determined after hydrolysis with thermostable α-amylase and amyloglucosidase, followed by a determination of the released glucose using an enzymatic colorimetric assay kit (Glucose CII-test, Wako Pure Chemical Industries, Ltd.). 18 Results were corrected to a starch basis by multiplying them by 0.9. Total fecal nitrogen was determined by Kjeldahl's method, 19 and results were multiplied by 6.25 to calculate the amount of protein in the feces.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The concentrations of undigested starch in the feces were determined after hydrolysis with thermostable α-amylase and amyloglucosidase, followed by a determination of the released glucose using an enzymatic colorimetric assay kit (Glucose CII-test, Wako Pure Chemical Industries, Ltd.). 18 Results were corrected to a starch basis by multiplying them by 0.9. Total fecal nitrogen was determined by Kjeldahl's method, 19 and results were multiplied by 6.25 to calculate the amount of protein in the feces.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Table 3 shows that the feces of rats fed the 0.6% EGCG diet contained more starch than that of the control diet. Especially given that EGCG possesses the inhibitory activity for pancreatic a-amylase (18), it is acceptable to assume that appreciable amounts of undigested starch flowed into the large intestine, and were excreted in the feces. It is fair to say that dietary starch that reaches the large intestine could be a potential source of fermentable substrate for anaerobic bacteria, consequently leading to the production of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Before analysis, dried feces samples were ground by a grinder mill. Starch content in feces was determined after hydrolysis with thermostable a-amylase and amyloglucosidase (Wako Pure Chemical Industries, Ltd., Osaka, Japan), followed by a determination of the released glucose using an enzymatic colorimetric assay kit (Glucose CIItest, Wako Pure Chemical Industries, Ltd.) (18). Results were corrected to a starch basis by multiplying them by 0.9.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…It was found that gallated catechins, that is, ECg and EGCg, showed higher renin-inhibitory activities than the ungallated forms, suggesting that esterification with gallic acid could lead to quite favorable influence on elevating the renin-inhibitory activities of EC and EGC. Previous work reported that catechins with a galloyl moiety presented higher activities in various cases than those without this moiety, for example, with respect to inhibiting fatty-acid synthase (25), suppressing postprandial hypertriglyceridemia (19) and modulating the intestinal digestion of dietary starch (24). In the present study, taking into consideration that gallic acid itself exerted good renin-inhibitory activity close to that of ECg, it could be speculated that the galloyl moiety might be a critical structure for the inhibitory activities of catechin-related compounds against renin.…”
mentioning
confidence: 99%